Os sentidos de escravo em Memórias Póstumas de Brás Cubas - Santos Júnior, Gilberto Egydio dos (Universidade Federal de São Carlos, 2019)
This work aims at a semantic analysis, with an enunciative basis, taking into account the history, the political and the social to understand The Senses of Slave in The Posthumous Memoirs of Brás Cubas, by Machado de Assis. For that, this study is carried out based on textuality procedures, which analyze rewriting and articulation, according to Guimarães (2018), verifying the relations of determination of the word slave in the text. As a methodological tool, we will use the Semantic Domain of Determination (DSD) device, Guimarães (2007), to identify the slave designation in Brás Cubas. In addition, from the notion of politician in Rancière (1996), more specifically by the Guimarães approach (2005), we will observe the normativity that happens within the enunciative space of the text, being this a factor of interference in the meaning of slave in the novel.
The senses of slave in the Posthumous Memoirs of Brás Cubas
Keywords: Semântica; Designação; Machado; Escravo; Acontecimento; Semantics; Designation; Slave; Literature; Event; Memórias póstumas; Posthumous memoirs; LINGUISTICA, LETRAS E ARTES::LINGUISTICA